ЭФФЕКТИВНОСТЬ ФОНДОВЫХ РЫНКОВ РАЗВИВАЮЩИХСЯ СТРАН БАЛТИЙСКОГО РЕГИОНА В УСЛОВИЯХ «ТОНКОЙ ТОРГОВЛИ» - Досмухамбетова, Г Б (Journal of Economic Research & Business Administration, 2015)
Paper tests impact of nonlinearities thin trading and changes of regulatory framework on ongoing market efficiency of three Baltic markets (Estonia, Latvia, Litva). Employing methodology proposed by Antoniou et. al. we test for EMH and using GARCH-in-mean specification we also gauge whether nonlinearities is driven by thin trading or by timevarying risk-premia? We assert that all three markets become efficient after adjusting for thin trading. In a nutshell we conclude that institutional evolution has positive impact in terms of market efficiency.